A Prospective Comparison of the 30-Minute and 60-Minute Oxytocin Dose Incremental Schedules for Induction of Labor at Term - Ade-Oju, Idowu P; Kuti, Oluwafemi; Loto, Olabisi M; Ogunniyi, Solomon O (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aim: To compare the efficacy and safety of two oxytocin incremental protocols used for induction of labor in women of low parity. Method: One hundred and twenty women (120) of low parity requiring induction of labour at term were randomly assigned into the two oxytocin induction dose protocols of the 30-minute and 60-minute incremental intervals. Induction–onset of labour interval, Induction-delivery interval, Delivery outcome and perinatal outcome were compared. Results: The induction-onset of labour interval and the induction delivery interval were comparable between the 60-min group and the 30-min group. Intrapartum complications like fetal distress, uterine hyperstimulation and precipitate labour were more common in the 30-min group however, this was not statistically significant. Conclusion: Oxytocin infusion regimens of 60-min and 30-min are comparable in outcome for induction of labour. The 60-min group carries less risk to both the mother and the fetus. Keywords: Induction-delivery interval, Induction of labor, oxytocin DOI: http://dx.doi.org/10.3126/njog.v6i1.5250 NJOG 2011; 6(1): 35-40